Microsatellite Analysis of Geographically Close Isolates of Cystoisospora suis - Joachim, Anja; Ruttkowski, Bärbel; Palmieri, Nicola (Frontiers in Veterinary Science, 2019)
Microsatellites are short repetitive DNA sequences of two to six repeats interspersed in the genome that display a rapid mutation rate and consequently show high variation between individuals or populations. They have been used to characterise population diversity and structure and the level of variation between different isolates of a number of different organisms, including apicomplexan protozoa. Currently nothing is known about the genetic variability and population structure of Cystoisospora suis (Apicomplexa: Coccidia), the causative agent of piglet coccidiosis, and we made use of the recently available genome of C. suis (strain Wien-I) to amplify microsatellite regions (ca. 300-550 bp) and evaluate the applicability of fluorescence-labelled primers to investigate amplicon length variation at high resolution using capillary electrophoresis (CE). Two phenotypically characterised isolates (Wien-I, toltrazuril susceptible; Holl-1 toltrazuril resistant) and six field isolates from Europe were compared by conventional PCR followed by agar-gel electrophoresis, Sanger sequencing and CE (fluorescence labelling and fragment length analysis) to evaluate the applicability of the method. Four primer pairs could be identified that amplified bands of the expected size and were labelled for CE analysis. High resolution CE for size determination of PCR amplicons proved to be a reliable and simple method. It revealed high diversity of the analysed strains, with marked differences even between two strains from neighbouring swine farms. In follow-up studies, adaptation of the PCR assay to multiplexing and amplification of small DNA quantities will provide a cost-effective tool to analyse field strains to reveal geographic diversity that could be mapped to phenotypic traits